Pancasila dan Harmonisasi Hukum Islam dalam Konteks Perkawinan: Pancasila and Harmonization of Islamic Law in the Context of Marriage - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Syihaabuddiin 'Askar; Mohammad Omar Hanif; Muhammad Fadli Bahtiar (DIRASAH: Jurnal Kajian Islam, 2025)
Pancasila, as Indonesia’s state ideology, serves as a guiding principle in regulating various aspects of life, including marriage law. Marriage, as both a social and religious institution, carries complex legal dimensions, particularly for Muslims where Islamic law holds significant influence. However, as a Pancasila-based state that values diversity, marriage regulations must reflect principles of justice, unity, and human rights while accommodating religious law. This article aims to analyze how Pancasila principles contribute to harmonizing Islamic law with national law in Indonesia’s marriage context. Using normative and socio-legal approaches, this study examines the Marriage Law No. 1 of 1974 and the Compilation of Islamic Law (KHI). Findings highlight that Pancasila’s principles of deliberation and social justice provide a foundation for integrating religious and national values. This harmonization ensures that marriage regulations not only align with Islamic legal principles but also uphold democratic values and constitutional rights. The article also emphasizes the need for inclusive policymaking to sustain religious values in a pluralistic society. This study aims to foster a deeper understanding of Pancasila’s role in reconciling Islamic law with national legal frameworks and its implications for developing fair and harmonious regulations. Such legal harmonization not only promotes social justice but also strengthens national unity within the framework of peaceful religious coexistence.